Continuum of Care Among People Living with Perinatally Acquired HIV Infection in New York City, 2014. (July 2016) - Xia, Qiang; Shah, Dipal; Gill, Balwant; Torian, Lucia V.; Braunstein, Sarah L.
Objective: The HIV care continuum outlines the steps from HIV infection to diagnosis, linkage to care, and viral suppression among people living with HIV. We examined data for steps along the HIV care continuum among people living with perinatally acquired infection in New York City using surveillance data. Methods: This study included data for people who acquired HIV infection perinatally and lived in New York City as of December 31, 2014. We defined "in care" as having ≥1 CD4 or viral load test in 2014, "in continuous care" as having ≥2 CD4 or viral load tests ≥3 months apart in 2014, and "virally suppressed" as having a viral load of ≤200 copies per milliliter in the most recent test in 2014. We estimated factors associated with viral suppression from a weighted log-binomial regression model that included sex, race/ethnicity, age, and country of birth as independent variables. Results: As of December 31, 2014, an estimated 1, 596 people were living with perinatally acquired HIV infection in New York City. All were diagnosed, 96% were in care, 80% were in continuous care, and 61% were virally suppressed. The multivariable analysis showed significant differences in viral suppression by race/ethnicity and age. Black patients (59%, 534/907) were the least likely of all racial/ethnic groups examined to have a suppressed viral load. By age, compared with 73% (80/109) of children aged 0–12 years who were virally suppressed, 58% (568/987) of adults aged 20–29 years and 56% (54/96) of adults aged 30–39 years were virally suppressed; the adjusted prevalence ratio was 0.80 (95% confidence interval [CI] 0.69, 0.92) for those aged 20–29 years and 0.79 (95% CI 0.63, 0.99) for those aged 30–39 years. Conclusion: The low level of viral suppression among people living with perinatally acquired infection found in this study warrants further exploration to identify the best management strategies to improve viral suppression in this population, especially those transitioning from pediatric to adult health care.